2003
DOI: 10.1152/ajpgi.00230.2002
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents alcohol-induced liver disease in rats by inhibiting the expression of NF-κB-dependent genes

Abstract: Induction of NF-kappaB-mediated gene expression has been implicated in the pathogenesis of alcoholic liver disease (ALD). Curcumin, a phenolic antioxidant, inhibits the activation of NF-kappaB. We determined whether treatment with curcumin would prevent experimental ALD and elucidated the underlying mechanism. Four groups of rats (6 rats/group) were treated by intragastric infusion for 4 wk. One group received fish oil plus ethanol (FE); a second group received fish oil plus dextrose (FD). The third and fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
183
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(201 citation statements)
references
References 37 publications
15
183
2
1
Order By: Relevance
“…Mucoprotective agents such as prostaglandin, glutathione, ornoprostil, sucralfate, and misoprostol have been found to exert protective effects on ethanol-induced gastric damages [27]. In addition to these compounds, natural extracts such as green tea extracts, wogonin, and curcumin showed a potential protective effect against alcoholic diseases [28][29][30]. Our present findings suggest that ginseng, the root of Panax ginseng C.A.…”
Section: Discussionsupporting
confidence: 50%
“…Mucoprotective agents such as prostaglandin, glutathione, ornoprostil, sucralfate, and misoprostol have been found to exert protective effects on ethanol-induced gastric damages [27]. In addition to these compounds, natural extracts such as green tea extracts, wogonin, and curcumin showed a potential protective effect against alcoholic diseases [28][29][30]. Our present findings suggest that ginseng, the root of Panax ginseng C.A.…”
Section: Discussionsupporting
confidence: 50%
“…Curcumin is the main active ingredient in turmeric 9 , and research has shown that it has some therapeutic effect on NAFLD 10,11 . However, the specific mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacokinetic feature of curcumin, which has been observed across several species, is the result of poor absorption and avid metabolic conjugation and reduction Sharma et al, submitted for publication). Despite the evidence that curcumin is poorly available following oral administration, there are reports that curcumin at 50 -200 mg kg À1 doses exerts biological activity on sites distant from the locus of absorption in rodents, such as breast (Inano and Onoda, 2002), prostate (Frank et al, 2003), lung (Menon et al, 1995) and especially the liver (Busquets et al, 2001;Park et al, 2001;Nanji et al, 2003). Studies on gall bladder contractility following oral curcumin in humans suggest that curcumin may exert biological actions at doses of 20 mg (Rasyid & Lelo 1999;Rasyid et al, 2002).…”
mentioning
confidence: 99%